Assessing the Compatibility of Non-Language Learning Games for Language Education: Development of the FUN (Functionality-Usability-Normality) Framework - Novianni Anggraini; SF Luthfie Arguby Purnomo; Arina Rohmatika (STAI Hubbulwathan Duri, 2026)
The increasing integration of digital games into informal language learning has highlighted the potential of commercial, non-language-learning games as supplementary pedagogical tools. However, educators lack a systematic framework to evaluate their compatibility with language learning objectives, particularly in genre-based instruction. This study addresses this gap by developing a practical evaluative framework for selecting suitable games. A qualitative design was employed using a Focus Group Discussion (FGD) involving eight experts in game-based learning, game design, and applied linguistics. Data were collected through a structured online discussion and analyzed using Spradley’s developmental research sequence, including domain, taxonomy, componential, and cultural theme analysis, guided by theories of game functionality, genre-based pedagogy, ergodic texts, and gamification. The analysis resulted in the development of the FUN framework, consisting of three dimensions: Functionality, Usability, and Normality. Functionality examines the alignment between game genres and targeted text genres through interpretive, explorative, and configurative user functions. Usability addresses platform accessibility and learner familiarity, influencing implementation feasibility. Normality evaluates socio-cultural appropriateness and potential distractions. These dimensions are operationalized into a compatibility rubric with three levels: compatible, appropriate, and discordant. The FUN framework provides a structured and practical tool for educators to evaluate and integrate commercial games into language learning contexts. While conceptually robust, the framework requires further empirical validation in classroom settings. Future research should examine its effectiveness in improving instructional decision-making and learning outcomes.